Digital Transformation in Accounting: Modern Technologies and Ethical Dilemmas Reshaping Financial Management and Reporting [całość] - Nita, Bartłomiej. Redakcja; Wanicki, Piotr. Redakcja (Publishing House of Wroclaw University of Economics and Business, 2025)
[How are digital technologies transforming finance and reporting — and what ethical challenges arise as a result? This monograph, edited by Bartłomiej Nita and Piotr Wanicki, synthesizes the latest research on the digital transformation of accounting, combining a rigorous methodological approach with insights from financial management practice. The authors provide a comprehensive literature review (based on Scopus and Web of Science) and identify four key thematic clusters: The evolving role of CFOs and financial managers Audit, control, and regulatory frameworks Decision-making, cybersecurity, and early warning systems Financial and non-financial reporting. Each cluster explores the impact of AI, data analytics, cloud technologies, and blockchain — alongside the related ethical risks and governance challenges. The publication concludes with concise research implications and future directions relevant to academics, practitioners, and regulators. Who is it for? • Researchers and PhD students in accounting, auditing, and fintech • CFOs, controllers, auditors, and ESG reporting professionals • Regulators and standard-setters • Business students seeking an overview of the latest trends in digital finance. Selected contents Methodological introduction The role of financial managers (CFOs) Audit, control, and regulations Decision-making, cybersecurity, and early warning signals Financial and non-financial reporting Conclusions and synthesis.] z zapowiedzi
s. 131
Keywords: digital accounting; artificial intelligence in finance; blockchain; data analytics; cybersecurity; early warning systems; audit financial and non-financial reporting; ethics